Pengaruh Budaya Organisasi, Pelatihan Kerja , Dan Pengembangan Karir Terhadap Kinerja Karyawan Pada PT. Perkasa Internusa Mandiri Medan - Sefriani Sinaga; Vetriana Zebua; Demak Claudia Yosephine Simanjuntak (Journal of Economic, Bussines and Accounting (COSTING), 2021)
This research aims to provide empirical evidence regarding the organizational culture of job training and development career on employee performance at PT. Perkasa Internusa Mandiri Medan in the future by testing each variable. The population in this study were 110 employees and a sample of 52 people. The research method used is multiple linear regression analysis. The results of the calculation of the partial hypothesis testing obtained the organizational culture value of 3,264 > ttebel (2,010) or the probability of sig (0,000) < 0,05, promotion (2,648) > (2,010) or probability sig (0,002) < 0,05,career development (4,966) > (2,010) or probability sig (0,003) < 0,05and the value of fcount (10,451) > Ftable(2,79) or probability sig (0,000) < 0,05. So the variables of organizational culture, job training and career development simultaneously have an effect or positively and significantly on employee performance variables at PT. Perkasa Internusa Mandiri Medan. The results of the test of the coefficient of determination obtained R Square sebesar 0,85. The indicates that 85% of organizational culture variables, job training and career developnent are able to explain the performance variables of cloud employees at PT. Perkasa Internusa Mandiri Medan the rest 15% (100% - 85%) is an influence. Fro,other unexplained independent variables such as work discipline variables such as work discipline variables and employee motivation. Keyword: Organizational Culture, Job Training, Career Development and Employee Performance